Treatment of iron-deficiency anaemia in pregnancy and postpartum - Breymann, Christian (2013)
It is clear that iron-deficiency states and anaemia should be treated. Even in milder forms of anaemia, it is often impossible to predict the course of the condition, or whether the situation is likely to worsen, and maternal and foetal risks increase as anaemia becomes more severe. Factors to be taken into account when deciding on the treatment approach to use include the time remaining until delivery, the severity of the anaemia, additional risks (e.g. premature labour), maternal co morbidity and the patient’s own wishes (e.g. refusal to receive donor blood to treat severe anaemia). Thus, for example, a Jehovah’s Witness with  severe anaemia two weeks before term needs different treatment than a woman with moderate anaemia and no additional risk factors during the second trimester. At present, the main treatment options for anaemia include oral iron, parenteral iron, the stimulation of haemopoiesis with growth factors (e.g. recombinant human erythropoietin) and the administration of heterologous blood.